René Girard on Job: the question of the scapegoat - Levine, Baruch A. (René Girard and biblical studies, 1985)
Abstract: The book of Job must be studied within the context of biblical literature, culture and society, with attention to the role of languages in the interpretation of ancient classics, and to literary motifs in ancient Near Eastern perspective. Biblical applications of the scapegoat phenomenon to humans is quite different from what we find in Job, as we see with reference to Lev 16 and other "riddance" rites. The servant song of Isa 52-53 tells how the scapegoat differed from other sufferers. There is no connection between the well-being of the community and the sufferings of Job, whose laments admit of a psychological explanation. His heroic dissidence is not a scapegoat phenomenon. (Source: Religion Index)